ДІАГНОСТИЧНІ КРИТЕРІЇ ЧОЛОВІЧОЇ ІНФЕРТИЛЬНОСТІ: ОГЛЯД ЛІТЕРАТУРИ ТА РЕЗУЛЬТАТИ ВЛАСНИХ СПОСТЕРЕЖЕНЬ (World Science, 2020)
The main diagnostic criteria for determining male infertility are provided in the article. The authors considered the mechanisms of impaired spermogenesis under the influence of unfavourable professional factors on the example of the evaluation of endocrine status, spermogram indicators and ultrasound examination of blood flow in the main testicular vessels of 187 patients who were exposed to low (43) or high (38) temperatures during their professional activity, worked under conditions of prolonged stress (58 people), were in contact with agricultural fertilizers and toxic chemicals (48 people) and 25 healthy men (control group). The results of the study conducted by the authors indicate a number of disorders of the morpho-functional state of sperm in men, depending on the specific production environment. The data obtained can be further used to develop a scientifically proven algorithm for correction of the discussed pathology, which is of great practical importance for family doctors, specialists in reproductologists, urologists and doctors dealing with occupational diseases.